Sosialisasi Aktivitas Fisik pada Lansia di Desa Cot Yang Kecamatan Kuta Baro Kabupaten Aceh Besar - Syukriadi Syukriadi; Nurul Amna; Suci Mayatara; Sahla Rizkina (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2023)
The importance of physical activity for the elderly in an effort to support indicators of healthy Indonesia, namely increasing the Life Expectancy of the Indonesian people. The purpose of this socialization is to find out the elderly's routine in daily activities to support Activity Daily Living (ADL). The method used in this outreach was the lecture and question and answer method, then questionnaires were distributed before and after the counseling to determine the elderly's understanding regarding physical activity. Suggestions for this activity are the elderly in Cot Yang Village, Aceh Besar District. This socialization activity was carried out for 1 hour. The results obtained from this socialization activity were that there was a change in the understanding of the elderly regarding physical activities carried out in daily activities. At this activity Mr. Geusyik, Village Secretary and Cot Yang Village Cadres along with 18 elderly people were present. Held on Friday 12 January 2024 at the Cot Yang Village multipurpose hall, at 09:00 WIB. This socialization activity was carried out by lecturers and Diploma Three Nursing students.